Obtaining of hydration parameters of cesium halides in the processes of water absorption and desorption - Vashchenko, O.V. (Functional Materials, 2014)
Cesium halides were examined in water absorption/desorption processes. A methodology was proposed to obtain hydration parameters of the substances examined. It was established that amount of water in near hydration shell as well as water desorption enthalpy increase in order CsCl-CsBr-CsI. Magnitudes of near hydration shell were established by means of thermogravimetry as 41, 86 and 99 water molecules, correspondingly.